PERUBAHAN INTENSITAS NYERI SENDI RHEUMTOID ARTRITIS PADA LANSIA DENGAN PEMBERIAN TEKNIKRELAKSASI KOMBINASI KOMPRES HANGAT DAN DINGIN - Kusmindarti, Indah; Virda Yuniarti, Enny (JURNAL KEPERAWATAN BINA SEHAT, 2014)
Rhematoid arthrithisin elderlycanincrease pain level because there is an inflamation. One of therapy non farmacologic that use to decrease pain level by use combination warm and cold compress. Warm and cold compress believed can increase threshold of pain. The purpose of this research is to make true there is or there is not influence warm and cold compress technique to change joint pain level in elderly with rheumatoid arthritis. The research method is pra experiment with one group pre test-post test design. Sample in this research is all number population elderly with Rheumatoid Arthritis that choose with total sampling technique with total respondent 18 respondents. Instrument that use in this research is protap warm and cold compress. The result of statistic test with descriptive modus used SPSS for windows show the value of modus before give an action is 3,00 that is mean reasonable level of pain and the value after give an action is 2,00 that is mean categories abated pain. That mean there is influence relaxation combination warm and cold to change pain level in elderly with rheumatoid arthritis. Gate control theories said that kuataneus stimulation warm and cold compress activated neuron big sensor A-beta if stimulus taktil that domination in subtanciesgelatinose will meet pain gate that make sinap gate close the transmission or stimulus obstruct and influence decrease the joint pain level. Based from the result of research above, combination warm and cold compress can adopt by respondent for decrease joint pain level out of farmacologic therapy.Key word : warm and cold compress,rheumatoid arthrithis pain